Construction Economics : A new approach - Myers, Danny (London : Taylor & Francis, 2008)
Students across a wide range of disciplines, ranging from construction management and construction engineering through to architecture, property and surveying should find this an invaluable textbook.
Previous ed.: London: Spon, 2004.
Includes bibliographical references (p. 309-316) and index.
Keywords: Construction industry -- Economic aspects; Industry